p53-Degradation by HPV-16 E6 preferentially affects the removal of cyclobutane pyrimidine dimers from non-transcribed strand and sensitizes mammary epithelial cells to UV-irradiation - El-Mahdy, Mohammed A; Hamada, Farid M; Wani, Manzoor A; Zhu, Qianzheng; Wani, Altaf A (Mutation research, 2000)
Nucleotide excision repair (NER), the most versatile and ubiquitous mechanism for DNA repair, operates to remove many types of DNA base lesions. We have studied the role of p53 function in modulating the repair of DNA damage following UV irradiation in normal and p53-compromised human mammary epithelial cells (HMEC). The effect of UV-induced DNA damage on cellular cytotoxicity and apoptosis was determined in conjunction with global, gene- and strand-specific repair. Cytotoxicity studies, using clonogenic survival and MTT assays, showed that HPV-16 E6-expressing HMEC were more UV sensitive than p53-WT cell lines. High apoptotic index obtained with p53-compromised cells was in conformity to both the low clonogenic survival and the low cellular viability. No discernible differences in the formation of initial UV-induced cyclobutane pyrimidine dimers (CPD) were observed in the cell lines of varying p53 functional status. However, the extent and the rate of damage removal from genome overall were highest for p53-WT cells. Further examination of strand-specific repair in the p53 gene revealed that the removal of CPD in the non-transcribed strand (NTS) was slower in p53-compromised cells compared to the normal p53-WT cell lines. These results suggest that loss of p53 function, in the absence of other genetic alterations, decreased both overall amount of CPD repaired and their removal rate from the genome. Additionally, normal function of p53 is required for the repair of the NTS, but not of the transcribed strand (TS) in genomic DNA in human epithelial cells. Thus, failure of quantitative removal of CPD by global genomic repair (GGR), due to loss of p53 function, causes the enhanced UV sensitivity and increased damage-induced apoptosis via a p53-independent pathway. Nevertheless, recovery of cells from UV damage requires normal p53 function and efficient GGR.